The Effect of Weblog (blog) students' writing performance - (:unkn) unknown (ELSEVIER SCIENCE BV, 2010)
With the recent advances in internet, the writing instruction that is proved to produce positive effect writing performance has taken a new trend. Due to such limitations of school setting as time restriction, lack of opportunity for students to reach a real audience or to satisfy their individual learning needs it has been understood that effective implementation of writing instruction is not so easy in practice. This understanding has led to the integration of weblogs in writing instruction. In this study; it has been investigated the effect of weblog integrated writing instruction on students writing performance. Total 70 Primary School students participated in the study. Data were collected through students, written products. Results indicated that weblog integrated writing instruction improved students. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Blog; weblog; educational technology; e-learning; writing